A peripheral polis in the Greek World? Pharos, the ‘apoikia’ of Paros on the coast of Croatia - de Angelo Laky, Lilian (Romanitas - Revista de Estudos Grecolatinos, 2023)
In this article, I will present the materiality of the urban area and territory of Pharos, the foundation of the Aegean polis of Paros, which took place at the beginning of the 4th century BC on the island of Hvar, located in Central Dalmatia, one of Croatia’s coastal regions. Historiography on Greek colonisation considers Dalmatia (and the polis in that area) to be a peripheral zone of Greek expansion, mainly because it occurred during a phase considered to be the decline of this phenomenon (Classical and Hellenistic periods). However, the material and literary evidence on Pharos shows a typical Greek city from the point of view of its physical and political organisation, very connected with its metropolis and other regions, even though it was located far from the main Greek centers in the Mediterranean (Aegean Sea, Ionian Sea and Tyrrhenian Sea).